2011
DOI: 10.3758/s13420-011-0018-6
|View full text |Cite
|
Sign up to set email alerts
|

Renewal after the extinction of free operant behavior

Abstract: Four experiments were performed to explore the role of context in operant extinction. In all experiments, leverpressing in rats was first reinforced with food pellets on a variable interval 30-s schedule, then extinguished, and finally tested in the same and a different physical context. The experiments demonstrated a clear ABA renewal effect, a recovery of extinguished responding when conditioning, extinction, and testing occurred in contexts A, B, and A, respectively. They also demonstrated ABC renewal (wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

53
366
5
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(440 citation statements)
references
References 38 publications
53
366
5
2
Order By: Relevance
“…Finally, transitioning to yet another novel Context C while extinction remained in effect produced an increase in responding (i.e., renewal). Relevant to our study, Todd et al found greater increases in responding in Context C when Context B was more distinct from Context C. Although ABC renewal tends to be smaller than ABA renewal (e.g., Bouton et al, 2011;but see Todd, 2013), renewal occurred to a level comparable to that of returning the subjects to the original training Context A (i.e., ABA renewal) when Context B was not explicitly made more distinct. These data are in accord with the results of the present study, where resurgence tended to be more evident following more discriminable transitions from reinforcement to extinction of alternative responding (i.e., signaled vs. unsignaled probes).…”
Section: Discussionmentioning
confidence: 69%
“…Finally, transitioning to yet another novel Context C while extinction remained in effect produced an increase in responding (i.e., renewal). Relevant to our study, Todd et al found greater increases in responding in Context C when Context B was more distinct from Context C. Although ABC renewal tends to be smaller than ABA renewal (e.g., Bouton et al, 2011;but see Todd, 2013), renewal occurred to a level comparable to that of returning the subjects to the original training Context A (i.e., ABA renewal) when Context B was not explicitly made more distinct. These data are in accord with the results of the present study, where resurgence tended to be more evident following more discriminable transitions from reinforcement to extinction of alternative responding (i.e., signaled vs. unsignaled probes).…”
Section: Discussionmentioning
confidence: 69%
“…One question about the data reported by Bouton et al (2011) was the size of the ABC renewal effect. Although statistically robust (e.g., 15 of 16 rats responded more in Context C than in Context B during testing), the increase in the rate of leverpressing from the context of extinction to the test context was not especially large numerically, and clearly was not as large as in ABA renewal.…”
mentioning
confidence: 99%
“…A recent series of experiment by Bouton, Todd, Vurbic, and Winterbauer (2011) demonstrated three forms of renewal following instrumental extinction. In one experiment, renewal of instrumental responding occurred when extinction took place in Context B and testing occurred in Context A (ABA renewal).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the renewal effect can occur in situations in which acquisition, extinction, and testing all take place in different contexts (ABC renewal; e.g., Bouton & Bolles, 1979) or in which the context changes only between extinction and testing (AAB renewal; e.g., Bouton & Ricker, 1994). Renewal can be found in many different preparations, including autoshaping with pigeons (Swartzentruber, 1993), human predictive learning (Üngör & Lachnit, 2006(Üngör & Lachnit, , 2008, and operant conditioning in rats (Bouton, Todd, Vurbic, & Winterbauer, 2011).…”
mentioning
confidence: 99%